The prevalence, pathophysiology, and treatment of fecal incontinence in patients with Crohn’s disease: a systematic review and meta-analysis - Shi, Yuting; Zhu, Yujia; Lan, Yixin; Xu, Li (Frontiers in Medicine, 2025)
BackgroundFecal incontinence (FI) is a common complication in patients with Crohn’s disease (CD), but there is a relative lack of comprehensive information on its prevalence, pathophysiology, and treatment interventions. This study aims to systematically evaluate the prevalence, pathophysiology, and treatment interventions of FI in patients with CD, providing a reliable dataset for clinical reference.MethodsAs of October 2024, articles were identified through a comprehensive search of PubMed, Web of Science, The Cochrane Library, Embase, and Scopus databases. The review included literature on the prevalence, pathophysiology, and treatment interventions for FI in patients with CD. Using the Stata 14.0 software package, the prevalence of FI among patients with CD was estimated with a random-effects model. Heterogeneity was assessed by calculating the I2 statistic and reporting the p-value from the chi-squared test for heterogeneity. Sensitivity analysis was performed to evaluate the robustness of the pooled effect estimate. Subgroup analysis and meta-regression were conducted based on various study characteristics, such as study design, sample size, and geographic region, to identify potential sources of heterogeneity. Publication bias was assessed using Egger’s test. Due to the inability to pool data across studies, risk factors, pathophysiology, and treatment interventions were described qualitatively.ResultsIn this analysis, a total of 25 studies were included. Fifteen of these studies assessed the prevalence of FI among 7232 patients with CD, yielding a pooled estimated prevalence of 34.8% (95% CI: 24.0%–46.5%). Six studies investigated the pathophysiology, suggesting that FI may be associated with decreased anal resting pressure, rectal compliance, and altered rectal sensation. Five studies evaluated potential treatment interventions, indicating that neuromodulation therapies such as posterior tibial nerve stimulation and sacral nerve stimulation may be effective for FI. Anti-tumor necrosis factor therapy in conjunction with surgical interventions may improve FI. Furthermore, pelvic floor behavioral treatment may improve FI and enhance quality of life when pharmacological treatments are ineffective.ConclusionThis study provides insights into the prevalence, pathophysiology, and treatment interventions of FI among patients with CD. The findings indicate that the prevalence of FI in CD patients is 34.8%. Further research is necessary to gain a deeper understanding of the pathophysiology of FI and to develop effective management and treatment interventions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/displayy _record.php?ID=CRD42024583028, identifier CRD42024583028.